2022
DOI: 10.1111/jace.18307
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure transformation of a crystallized glass from the system BaO‐SrO‐ZnO‐SiO2

Abstract: Glass-ceramics from the studied system are able to precipitate a crystalline phase with an anomalous and low coefficient of thermal expansion. Besides the crystalline phase called LEAZit (Low Expansion Alkaline Earth Zinc Silicate), other phases appear within those glass-ceramics. In order to understand the thermal expansion behavior of the whole material, the phase content has to be known as a function of the composition and the chosen heat treatment. In this paper, a glass with the molar composition 5 BaO ⋅ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…An illustrative example is given in the following paragraph, whereas details of the study can be found in Ref. 40. Again, a glass ceramic from the system Ba 1‐ x Sr x Zn 2 Si 2 O 7 has been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…An illustrative example is given in the following paragraph, whereas details of the study can be found in Ref. 40. Again, a glass ceramic from the system Ba 1‐ x Sr x Zn 2 Si 2 O 7 has been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…19, it has been confirmed experimentally on similar glass compositions by EDX that the dark phase is enriched in SiO 2 . 68 The thermal expansion is strongly affected by the grain size of the used glass powder. In general, the CTE is more negative, if the used grain size is larger.…”
Section: Sinter Crystallization Of Glassesmentioning
confidence: 99%
“…19, it has been confirmed experimentally on similar glass compositions by EDX that the dark phase is enriched in SiO 2 . 68…”
Section: Sintering Of Glass Powders and Sol–gel Derived Glassesmentioning
confidence: 99%
“…[28] For instance, in a recent works, biodiesel has been sustainably produced by using SrO-ZnO/Al 2 O 3 as a bifunctional catalyst. [29,30] Other studies have explored the glass crystallization applications using these oxides, for example, BaO-SrO-ZnO-SiO 2 , [31] Eu 3þ doped SrO-ZnO-PbO-P 2 O 5 , [32] and BaO/SrO/ ZnO/SiO 2 . [33] In addition to these applications, owing to the non-toxic genesis of both oxides, they have also been used in the biological applications, i.e., ZnO and/or SrO acting as the therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%